DIVERSIFIKASI DAN DINAMIKA PENGHIDUPAN MASYARAKAT DI PULAU GUSUNG KELURAHAN GUNTUNG KOTA BONTANG - Emma Redjayanata; Bambang Indratno Gunawan; Gusti Haqiqiansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2014)
This study aims to analyse livelihood diversification and to determine livelihood dynamics of coastal community in Gusung Island Bontang City. The study was carried out from April to May 2014. The study site was in Gusung Island Guntung Village of BontangCity.Data were collected using survey method that consisted of qualitative and qualitative approaches. Primary data were gathered through field observation and in-depth interviews with respondents and key informants from various social actor categories including seaweed farmers, households leader, punggawa, community leaders, head of seaweed farmer group, fishers and women/wife of seaweed farmers.Results showed that according to diversification analysis coastal livelihoods in the area came from major source accounted for 69%, contributed from seaweed cultivation, and the remaining 31% from the livelihoods of fishers, traders, private company workers and Islamic teachers. Social actors those play an important role in Gusung Island are seaweed farmers, households’ leaders, punggawa and women/wife of sea weed farmers. There are livelihood dynamics in the studied area, i.e. the occurrence of permeable coastal boundaries, social exclusion and inclusion and migration.